To Evaluate Knowledge of Obstetric Danger Signs & Birth Preparedness of Women - HINA MASOOD, GUL E RAANA, MARIAM MALIK, AQUILA FAZIL (Journal of Fatima Jinnah Medical University, 2018)
Background: In a developing country like Pakistan, there is a great need to save mother and neonatal life. Government has launched many programs but due to lack of knowledge and approach of health care delivery system to people, we lose many lives daily. Lack of adequate knowledge, negative attitude and inadequate birth preparedness results in loss maternal and neonatal life. Birth preparedness is a plan of the process of childbirth and it involves choice of place of birth, arrangement for transportation, blood donors and knowledge of health facility. Objective: The objective of this study was to assess the knowledge of females towards obstetric danger signs and birth preparedness. Methodology: This cross-sectional study was conducted on 760 obstetric patients (antenatal as well as postnatal), in Gynae Unit 1, Sir Ganga Ram Hospital , Fatima Jinnah Medical College, Lahore. A questionnaire was developed containing socio-demographic information, reproductive history, basic knowledge about antenatal care, knowledge on high risk pregnancy signs and about birth preparedness in the presence of any danger sign. The data will be entered into SPSS version 20. Results: The mean age of females was 26.92±4.71 year. There were 34.4% primipara females , and 59.2% with parity 2-4. Regarding education status, 8.6% females were uneducated ,48.6% with primary level education and 34.2% females with secondary level education and only 8.6% were graduates. Majority 92.4% females were housewives. Most (95.8%) of females had basic knowledge about antenatal care importance. Out of all females, 350(46.1%) had less than 4 antenatal visits while 409 (53.9%) females had more than 4 antenatal visits. More than half (57.7%) females said that first antenatal examination should be done in the 1st trimester, one fourth (26.3%) said in 2nd trimester, while only(16.0%) said first antenatal examination should be done in 3rd trimester. Seventy five percent of the females had knowledge of the obstetric risks and danger signs of pregnancy and had positive attitude towards having antenatal care, going to health facility or health care provider and used benefits from health care system, and were birth prepared. Conclusion: Three fourth (75%) of women had knowledge of high risk pregnancy signs and 70% of them were birth prepared in a comprehensive way. It is concluded that more and more counseling and courses are required to improve the knowledge, attitude and practice of females as well as their families towards birth preparedness and complication readiness in rural as well as urban areas of Pakistan, thus decrease perinatal morbidity and mortality.